Pengembangan Lembar Kerja Siswa Berbasis Multiple Intelligence pada Materi Enzim Siswa SMA - Vera Duwi Lestari, Anista; Nisa, Khoirun (Biology Education Department, Universitas Insan Budi Utomo, Malang, Indonesia, 2018)
This research was conducted based on the problems that occurred, among others: LKS owned by students so far have not been able to train students to learn independently and low mastery of students on metabolic material. The purpose of this development research is to find out the development process and find out the results of the development of Multiple Intelligence Based Student Worksheets on the material of high school students' enzymes. This study uses the 4D development model by Thiagarajan et al. which includes 4 stages: Define, design, design and Disseminate. Testing of Multiple Intelligence-Based LKS products, there are several aspects including media assessment, assessment of material and readability tests. Multiple Intelligence-based worksheet validation results have been obtained by media expert validators with a percentage of 96.43%, by the material expert validator with a percentage of 84.21% and the students' readability trial results obtained a percentage of 65.33%. Based on the data that has been obtained for testing this Multiple Intelligence-Based LKS product, it is expected that in the future it can be tested on a large scale in the classroom for further development. Further development, can be done with classroom action training (PTK) or Experimental research.